SERONEGATIVE STIFF PERSON SYNDROME: A DIAGNOSTIC CHALLENGE IN THE ABSENCE OF ANTI-GAD ANTIBODIES - Dr Avesh Kumar; Dr Duroov Bhagat; Dr Brahma; Dr Ashar Shahid; Dr Syed Adan Hussain Naqvi; Mehak Devi (Journal of Medical & Health Sciences Review, 2026)
Background: Stiff Person Syndrome (SPS) is a rare autoimmune neurological disease, which is marked by progressive muscle rigidity and spasms, usually accompanied by anti-glutamic acid decarboxylase (anti-GAD) antibodies. Nevertheless, seronegative cases are a diagnostic dilemma since they do not exhibit characteristic serological markers. Case Presentation: We report a case of a 38-year-old male who presented with a one-year history of progressive stiffness and weakness of both upper limbs, predominantly affecting the hands. Neurological examination revealed increased muscle stiffness with preserved reflexes and normal sensory findings. Laboratory investigations including autoimmune and infectious workup were unremarkable, and anti-GAD antibodies were negative. Magnetic resonance imaging of the brain and cervical spine showed no significant abnormalities. Nerve conduction studies were normal, while electromyography demonstrated continuous motor unit activity, consistent with SPS. Conclusion: The case indicates the significance of considering SPS in patients with typical clinical and electrophysiological manifestations, despite the absence of serological markers. Seronegative SPS needs to be diagnosed at an early stage so that it can be managed properly and thus enhance the outcome of patients.